A cardiovascular dynamic analysis in zebrafish embryos reveals trifloxystrobin-induced cardiovascular dysfunction - Jiun-Lin Horng; Yueh-Tzu Kao; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Ammonia toxicity in medaka embryos involves ion depletion and internal organ apoptosis and its mitigation is by sodium-driven ammonia excretion - Li-Yih Lin; Po-Yen Chen; Xu-Zheng Qiu; Jiun-Lin Horng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Acute sublethal ammonia exposure suppresses neurotransmitter expression and impairs behaviors in the early development stages of zebrafish - Sian-Tai Liu; Li-Yih Lin; Meng-Shin Shiao; Ming-Yi Chou (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Novel self-assembled antimicrobial peptide Pardaxin hydrogel as a functional biomaterial for food packaging and preservation - Sanjay Prasad Selvaraj; Ju-Chun Chang; Karukuvelraja Raja; Jing-Ting Zhu; Prakash Kishore Hazam; Wen-Chun Lin; Jung-Ren Huang; Tsung-Lin Li; Jyh-Yih Chen (Chemical Engineering Journal, 2025)

Pluvial flood warnings in a tidally influenced basin enhanced by rainfall–tide compound indicators: Taipei case study - Mei-Ying Lin; Wen-Yih Sun; Huei-Syuan Fu; Chih-Hsin Chang; Wei-Bo Chen; Chieh-Ju Wang; Hsuan-Wei Wang; Yi-Chiang Yu; Yen-Wei Li (Stochastic Environmental Research and Risk Assessment, 2025)

Pyraclostrobin disrupts ion regulation by suppressing mitochondrion-rich ionocyte differentiation in zebrafish embryos - Li-Yih Lin; Fan-Hsuan Yeh; Kuan-Yi Lee; Jiun-Lin Horng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Assessing the toxicity of bongkrekic acid in zebrafish embryos - Jiun-Lin Horng; Kuan-Yi Lee; Jen-Leih Wu; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Evaluating N-acetylcysteine for mitigating cisplatin-induced oxidative stress and ionocyte damage in a zebrafish model - Szu-Jung Chen; Ciao-Ling Wu; Li-Yih Lin; Jiun-Lin Horng (Toxicology and Applied Pharmacology, 2025)

Sexual dimorphism in zebrafish aggression and metabolism under acute ammonia stress - Fang Zhi Chua; Li-Yih Lin; Yung-Che Tseng; Ming-Yi Chou (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Sublethal effects of acidified water on sensorimotor responses and the transcriptome of zebrafish embryos - Jiun-Lin Horng; Kuan-Yi Lee; Li-Yih Lin (Chemosphere, 2025)

Investigation of verapamil-induced cardiorenal dysfunction and compensatory ion regulation in zebrafish embryos - Jiun-Lin Horng; Bu-Yuan Hsiao; Wen-Ting Lin; Tzu-Ting Lin; Ching-Yen Chang; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Assessing cardiovascular toxicity in zebrafish embryos exposed to copper nanoparticles - Bu-Yuan Hsiao; Jiun-Lin Horng; Ching-Hua Yu; Wen-Ting Lin; Yu-Han Wang; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Acidified water promotes silver-induced toxicity in zebrafish embryos - Jiun-Lin Horng; Geng-Xin Kung; Li-Yih Lin (Aquatic Toxicology, 2024)

Investigation of ammonia-induced lethal toxicity toward ion regulation in zebrafish embryos - Li-Yih Lin; Chieh-An Cheng; Sian-Tai Liu; Jiun-Lin Horng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Fenpropathrin causes alterations in locomotion and social behaviors in zebrafish (Danio rerio) - Sian-Tai Liu; Jiun-Lin Horng; Li-Yih Lin; Ming-Yi Chou (Aquatic Toxicology, 2023)

Toxic effects of polystyrene nanoparticles on the development, escape locomotion, and lateral-line sensory function of zebrafish embryos - Li-Yih Lin; Phunsin Kantha; Jiun-Lin Horng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Sublethal effects of methylmercury on lateral line sensory and ion-regulatory functions in zebrafish embryos - Giun-Yi Hung; Yu-Chin Pan; Jiun-Lin Horng; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Exposure to silver impairs the osmoregulatory capability of euryhaline medaka (Oryzias latipes) subjected to salinity changes - Jiun-lin Horng; Ya-Shan Lee; Li-Yih Lin (Aquatic Toxicology, 2023)

Patient Confidential Information Transmission Using the Integration of PSO-Based Biomedical Signal Steganography and Threshold-Based Compression - Shih-Ying Chen; Shan-Ju Lin; Ming-Cheng Tsai; Ming-Dar Tsai; Yih-Jing Tang; Shuo-Tsung Chen; Li-Hsiang Wang (Journal of Medical and Biological Engineering, 2021)

Dynamic Stability of an Ocean Current Turbine System - Shueei-Muh Lin; Yang-Yih Chen; Hung-Chu Hsu; Meng-Syue Li (Journal of Marine Science and Engineering, 2020)
This paper presents a theoretical solution for the dynamic stability of the ocean current turbine system developed in Taiwan. This system is tethered to the sea floor and uses the Kuroshio Current to produce electricity. To maintain the performance of the turbine system in the presence of the Kuroshio Current, the stability of the surfaced turbine needs to be considered. The proposed system is composed of a turbine, a buoyance platform, a traction rope, and a mooring foundation. The two-dimensional theoretical solutions treat the turbine as a rigid body with a movable structure that is moored with two cables. In this model, the gravity, buoyancy, and drag force generated by the wave on the turbine structure are considered. In addition, an analytical solution is proposed for the general system. Finally, the effects of the wave on the pitch motion and dynamical stability of the ocean current turbine system are investigated.

Steroid-Enriched Fraction of Achyranthes bidentata Protects Amyloid β Peptide 1–40-Induced Cognitive Dysfunction and Neuroinflammation in Rats - Li-Wei Lin; Fan-Hsuan Tsai; Wan-Cheng Lan; Yih-Dih Cheng; Sheng-Chi Lee; Chi-Rei Wu (Molecular Neurobiology, 2019)

Time-dependent shake map for Uttarakhand Himalayas, India, using recorded earthquakes - Himanshu Mittal; Yih-Min Wu; Ting-Li Lin; Cédric P. Legendre; Sushil Gupta; Benjamin M. Yang (Acta Geophysica, 2019)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Sensitivity analysis of the hydrological response of the Gaping River basin to radar-raingauge quantitative precipitation estimates - Tsung-yi Pan; Meng-ying Li; Yong-jun Lin; Tsang-jung Chang; Jihn-sung Lai; Yih-chi Tan (Hydrological Sciences Journal, 2014)

A new model for fish ion regulation: identification of ionocytes in freshwater- and seawater-acclimated medaka (Oryzias latipes) - Hao-Hsuan Hsu; Li-Yih Lin; Yung-Che Tseng; Jiun-Lin Horng; Pung-Pung Hwang (Cell and Tissue Research, 2014)

Reduction of connexin43 in human endothelial progenitor cells impairs the angiogenic potential - Hsueh-Hsiao Wang; Cheng-Huang Su; Yih-Jer Wu; Jiun-Yi Li; Ya-Ming Tseng; Yi-Chun Lin; Chin-Ling Hsieh; Cheng-Ho Tsai; Hung-I Yeh (Angiogenesis, 2013)

The CAG repeat in SCA12 functions as a cis element to up-regulate PPP2R2B expression - Chih-Hsin Lin; Chiung-Mei Chen; Yi-Ting Hou; Yih-Ru Wu; Hsiu-Mei Hsieh-Li; Ming-Tsan Su; Guey-Jen Lee-Chen (Human Genetics, 2010)

Non-synonymous GIGYF2 variants in Parkinson’s disease from two Asian populations - Eng-King Tan; Chin-Hslen Lin; Chun-Hwei Tai; Louis C. Tan; Meng-Ling Chen; R. Li; Hui-Qin Lim; Ratnagopal Pavanni; Yih Yuen; K. M. Prakash; Yi Zhao; Ruey-Meei Wu (Human Genetics, 2009)

Juvenile Tilapia (Oreochromis mossambicus) Strive to Maintain Physiological Functions After Waterborne Copper Exposure - Su Mei Wu; Hui Ru Ding; Li-Yih Lin; Yu-Siang Lin (Archives of Environmental Contamination and Toxicology, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)